BURNOUT, SINTOMAS DEPRESSIVOS E ESTRATÉGIAS DE ENFRENTAMENTO EM RESIDENTES DE ENFERMAGEM - BARROS, ALBA L. B. L. D.; FRANCO, GIANFABIO P.; NOGUEIRA-MARTINS, LUIZ A. (Salão do Conhecimento, 2013)
Resumo